Budget constraints in party-states nested in power relations: the key to different paths of transformation - Maria Csanadi (Hungarian Academy of Sciences, Institute of Economics, 2004)
This paper revisits the widely known and used concept of soft budget constraints in party-states introduced by Kornai (1980), from the point of view of a comparative analytical model (Csanádi, 2003). It embeds budget constraints in the structure of power relations described by the model as the interactive structure of interrelations between party-, state- and economic decision-makers on the level of individual actors. In this respect, we argue, that soft budget constraints will acquire several new structure-specific traits presented in the paper that are worth to consider. The new properties of budget constraints nested in power relations will define the selectively soft and hard constraints of self-reproduction of the net. The distribution of power will define the dynamics of reproduction of the structure as a whole. The differences in the distribution of power will be responsible for the frequency of its hardening reproduction constraints. Soft and hard reproduction constraints and its dynamics in different power distributions will contribute to several theoretical conclusions concerning the selfsimilarities and structural differences in the operation and different paths of disintegration, collapse and transformations of party-states.
Keywords: 330; communism; socialism; party-state system; comparative model; soft budget constraint; selectivity; reproduction constraints; disintegration; collapse; transformation